A new species of Galathea Fabricius, 1793 (Crustacea: Decapoda: Anomura: Galatheidae) from Okinawa, southern Japan - Osawa, Masayuki; Higashiji, Takuo (Zootaxa, 2012)
A new species of squat lobster, Galathea chura sp. nov., is described from deep-waters off Okinawa Island in the Ryukyus,southern Japan, on the basis of a single specimen found on a colony of unidentified octocoral of the genus Parisis Verrill,1864. The new species resembles G. magnifica Haswell, 1882, G. spinosorostris Dana, 1852, and G. tanegashimae Baba,1969, in having scale-like or interrupted arcuate ridges on the gastric region of the carapace and epipods on the first or first and second pereopods only, but it is readily distinguished by the absence of epigastric spines.